Assessing the Hawthorne effect on hand hygiene compliance in an intensive care unit. Issue 2 (June 2020) - Bruchez, Solange Angelina; Duarte, Giulianna Chiqueto; Sadowski, Renata Alessandra; Custódio da Silva Filho, Ademir; Fahning, Wupiham Eloy; Belini Nishiyama, Sheila Alexandra; Bronharo Tognim, Maria Cristina; Cardoso, Celso Luiz
Summary: Background: The influence of the Hawthorne effect on hand hygiene compliance in an intensive care unit was assessed using covert and overt direct observation. Methods: The observational study was conducted from February to November 2018 in a 24-bed adult intensive care unit in a 243-bed tertiary care hospital, in four periods (P): P-1, February 5-March 3, 29 h (covert) and P-2, March 15-April 16, 33 h (overt), prior to an educational campaign on hand hygiene; and P-3, August 27-September 28, 33 h (covert) and P-4, October 3-November 6, 35 h (overt), after the campaign. Three 20-min observation sessions were performed daily, randomly distributed in the morning, afternoon and evening shifts, including holidays and weekends. Hand hygiene compliance rates observed in Periods 2 and 4 were displayed on an electronic panel installed in the unit. Hand hygiene compliance was assessed according to the World Health Organization "My Five Moments for Hand Hygiene" guidelines. Results: Before the campaign, the overall hand hygiene compliance rate was 31.95% (340/1064, covert) versus 68.10% (790/1160, overt), and afterwards was 56.11% (615/1096, covert) versus 80.98% (1086/1341, overt). The infection rate was reduced by 22.62% (18.87% versus 14.60%). Conclusions: The Hawthorne effect and educational campaign markedly influenced compliance with hand hygiene recommendations. The results suggest that combining overt and covert observation methods, including regular feedback on hand hygiene compliance displayed on an electronic panel, may be a valid alternative to increase real hand hygiene compliance rates in hospital practice.